Determining Factors Influencing Generation Z's Intention to Purchase Green Cosmetics - Hasesda, Sri Wulan Sari Adi Pandur; Yulianto, Edy; Fahrudi, Agung Nugroho Luthfi Imam (FIA UB, 2024)
Even though Indonesia is the largest cosmetic market growth country in Southeast Asia and is expected to continue to top that position for the next 10-15 years, however the awareness of green cosmetics still relatively low. By making Generation Z who are known to be more concerned about environmental issues and their contribution the national economics as respondents in this study, this study seeks to explain the factors that influence green purchase intention of green cosmetics in Indonesia. This study proposes a substitution of Subjective Norms in the Theory of Planned Behavior (TPB) with Personal Norms, which derived from the Norm Activation Model (NAM). This study introduces new integrated model TPB and NAM. This study deploys Green Purchase Attitude, Perceived Behavioral Control, as well Personal Norms predictors of Green Purchase Intention for The Body Shop products. Quantitative research approach and purposive sampling method were implemented to collect primary data using questionnaires to 165 consumers of The Body Shop of Indonesia. The results of the study show that Personal Norms and Perceived Behavioral Control are proven to significantly influence Green Purchase Intention. Meanwhile, Green Purchase Attitude has no significant influence on Green Purchase Intention for The Body Shop products in Indonesia.